2009
DOI: 10.1002/jhm.495
|View full text |Cite
|
Sign up to set email alerts
|

The role of physician engagement on the impact of the hospital‐based practice improvement module (PIM)

Abstract: BACKGROUND: Physicians play an important role in hospital quality improvement (QI) activities. The Hospital‐Based Practice Improvement Module (Hospital PIM) is a web‐based assessment tool designed by the American Board of Internal Medicine (ABIM) to facilitate physician involvement in QI as a part of maintaining certification. OBJECTIVE: The primary objective of this study is to explore the impact of the Hospital PIM on physicians participating in hospital‐based QI. DESIGN: Qualitative design consisting of sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…TCT measures evaluated in this study included participation in intervention components, perceptions of unit performance on infection prevention behavior, and key barriers to team progress including lack of leadership support and physician engagement, which are often central to implementation success [6,19-21]. Our study found support for the temporal stability, construct validity, and responsiveness of QI team member reports on intervention activities, perceived unit-level behaviors, and barriers to team progress from this instrument.…”
Section: Discussionmentioning
confidence: 68%
“…TCT measures evaluated in this study included participation in intervention components, perceptions of unit performance on infection prevention behavior, and key barriers to team progress including lack of leadership support and physician engagement, which are often central to implementation success [6,19-21]. Our study found support for the temporal stability, construct validity, and responsiveness of QI team member reports on intervention activities, perceived unit-level behaviors, and barriers to team progress from this instrument.…”
Section: Discussionmentioning
confidence: 68%
“…For example, through additional capital investments, an organization could easily modify such aspects of organizational infrastructure as information systems (e.g., data infrastructure) and general QI infrastructure (e.g., quality steering council or QI department). Similarly, there are many potential ways of increasing physicians’ involvement in QI, like aligning payment incentives and tying participation in QI to maintenance of board certification (Caverzagie et al 2009). If future research continues to support the ideas that the number of years an organization is involved in QI and the depth with which QI pervades the organization are important to QI success, it will be critical for organizations to continue the long‐term pursuit of QI across changes in leadership, economic climate, and policy.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36] Physicians describe having improved their ability to answer questions at the point-of-care, professionalism and teamwork behaviors, supervision of residents' clinical care, and general knowledge of quality improvement through MOC activities. [37][38][39][40][41] Although quality improvement is important to patient care, not all physicians understand how to apply the principles. Some studies note that practice-level collaboration and coaching may enhance the MOC practice improvement requirement.…”
Section: Learning and Improvementmentioning
confidence: 99%